Human resource management in the healthcare setting during COVID-19 pandemic: policy recommendations, implementation challenges, and the way forward - Azmi, Nazmi Ainaa; Mohamed Isa, Siti Zubaidah; Mahmud, Aidalina (Universiti Putra Malaysia, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic has caused a worldwide human resource crisis in the healthcare setting due to the continuous and overwhelming demand of the workforce. Failure in managing the human resource will negatively affect the clinical management, prevention, and control of the pandemic; while a well planned human resource policy can ensure sustainable and sufficient skilful workers to meet the demand. This article presents policies that are recommended by the World Health Organization (WHO) and other significant studies in addressing the issues faced by many countries during this COVID-19 pandemic. As with all policies, there are various challenges in the implementation of policies related to COVID-19. Therefore, this article also discusses the challenges in the implementation of these policies. This article ends with the proposal for the way forward in human resource management during a pandemic, should another pandemic hit the world.